Penerapan Metode Fuzzy Simple Additive Weigting Pada Interpretasi Hasil Penilaian Promosi Jabatan Pegawai Negeri Sipil - Reta, Tre Hayu Ria; Alisah, Evawati; Jauhari, Mohammad Nafie (Jurnal Riset Mahasiswa Matematika, 2023)
The Fuzzy Simple Additive Weighting (FSAW) method is a mechanism that can be used to support decision making. This method was chosen because a ranking process was carried out to determine the weight value of each attribute, which would select employees who were worthy of occupying the promoted position. This study aims to determine the results of the application of the FSAW method in the assessment of civil servant promotion at the Malang City Education and Culture Office to increase objectivity and fairness in the assessment of employee promotion. Some problems that often occur in employee evaluation are the employee evaluation process which is still conventional so that it is less effective in calculation. The solution to overcome this problem is to use a Fuzzy Multi Attribute Decision Making (FMADM) decision support system with the FSAW method. This method requires a process to normalize the decision matrix (X) against a scale that can be compared with all available alternative values.  After each attribute has been determined its weight value, the ranking process is used to select the best alternative for this study.  The criteria used in this decision support system are SKP score, length of service, class, and education. The membership function used is the Triangular Fuzzy Number (TFN) representation. The results of the ranking calculation or the best value show the highest value, namely 1 from alternative 1 (employee 1) who is entitled to a promotion. It is expected that by using the FSAW method, the task of selectors will be able to more quickly and precisely identify employees who are worthy of occupying positions promoted based on the desired conditions.